The role of attention and health goals in nudging healthy food choice - Gillebaart, Marleen; Blom, Stephanie S. A. H.; Benjamins, Jeroen S.; de Boer, Femke; De Ridder, Denise T. D. (Frontiers in Psychology, 2023)
Nudging is a promising intervention technique that supports people in pursuing their healthy eating goals. Recent research suggests that, despite previous assumptions, disclosure of the presence of a nudge does not compromise nudge effectiveness. However, it is unknown whether attention to a nudge affects nudge effects. We assessed the role of attention systematically, by examining explicit and implicit attention to nudges, while also exploring healthy eating goals as a potential moderator. Participants were assigned to a nudge (i.e., a shopping basket inlay with pictures of healthy items) or control condition (i.e., a shopping basket inlay with neutral pictures) and chose a snack in an experimental supermarket field study. Explicit and implicit attention (with a mobile eye-tracker) to nudges, healthiness of snack choice, and healthy eating goals were assessed. Results showed that attention to the nudge did not hamper the nudge's effect. Furthermore, individuals with strong healthy eating goals made healthier food choices in the nudge condition. Individuals with weak to non-existent healthy eating goals were not influenced by the nudge. Findings are in line with the viewpoint that nudging does not by definition work 'in the dark', and suggests that nudges support people in adhering to their healthy eating goal.